Modellierung und Simulation semi-transparenter organischer Solarzellen - Mescher, Jan (KIT Scientific Publishing, 2015)
In this work the electrical and optical properties of semi-transparent organic solar cells are investigated. For this purpose an optoelectronic simulation model is developed and simulated results and experimental data are compared to each other. Besides the efficiency of the solar cells this work puts a special emphasis on the color properties of the light, which is transmitted through the semi-transmitted solar cells.